Therapeutic implications for the PD-1 axis in cerebrovascular injury - James Feghali; Christopher M. Jackson (Neurotherapeutics)
Since the discovery and characterization of the PD-1/PD-L pathway, mounting evidence has emerged regarding its role in regulating neuroinflammation following cerebrovascular injury. Classically, PD-L1 on antigen-presenting cells or tissues binds PD-1 on T cell surfaces resulting in T cell inhibition. In myeloid cells, PD-1 stimulation induces polarization of microglia and macrophages into an anti-inflammatory, restorative phenotype. The therapeutic potential of PD-1 agonism in ischemic stroke, intracerebral hemorrhage, subarachnoid hemorrhage-related vasospasm, and traumatic brain injury rests on the notion of harnessing the immunomodulatory function of immune checkpoint pathways to temper the harmful effects of immune overactivation and secondary injury while promoting repair and recovery. Immune checkpoint agonism has greater specificity than the wider and non-specific anti-inflammatory effects of other agents, such as steroids. PD-1 agonism has already demonstrated success in clinical trials for rheumatoid arthritis and is being tested in other chronic inflammatory diseases. Further investigation of PD-1 agonism as a therapeutic strategy in cerebrovascular injury can help clarify the mechanisms underlying clinical benefit, develop drugs with optimal pharmacodynamic and pharmacokinetic properties, and mitigate unwanted side effects.